Meaning of work in life of the first Christian monks - Szewczul, Bożena (Prawo Kanoniczne, 2018)
Work, beside prayer, that is to say God’s service were the essence of the first Monks life, what was rightly described by Benedictines’ maxim: ora et labora. First representatives of the life, which was completely given to God in Catholic Church, strived to make their work a prayer at the same time, so they could keep constant relation with God. Main purpose of work, being a form of imitation of hard-working Christ and Apostles, was also participation in His redemptive work, and obtaining means needed for simple living, in accordance with evangelical poverty. Work had also ascetic aspect for Monks, because it gave possibility of overcoming their own weaknesses, more complete realization of requirements included in the Gospel, and at the same time more accurately becoming similar to Christ. Thanks to work the Religious could give help to the people in need. Basic rules regarding meaning, understanding, and performing work were given in Apophthegm of Desert Fathers, and Monastic Rules, whereas the rest had to be personally found out by each Monk, together with fulfillment of their duty performed in silence, and concentration, as well as obtaining experience in art of connecting prayer with work. At the same time they all were aware, that to be a real Monk meant “to work with their own hands”.